Theology in dialogue and dialogue in theology: Destroying the walls of hostility - Resane, K. Thomas (Verbum et ecclesia, 2022)
Dialogue has the power to calm the conflicts, misunderstandings and prejudices among people of different cultures, religions, theologies and worldviews. This article points out that theology and dialogue are inseparable. It endeavours to find a definition of dialogue and its role in theology and how theology expresses itself through dialogue. The church speaks through dialogue, and theology’s voice is heard mostly from and through the church. It is a dialogue that spearheads the shape and formation of theology. All the biblical dialogues are theological in content. The role played by the biblical text during the dialogical processes is very important. A theologian affirms and embraces the text through communicating with it. He or she must always attempt to engage the movements and the thoughts of the text. Texts are primarily powerful instruments of groups and only second-line power tools of individuals. The principles of comparative theology are ideal in any dialogue. Dialogues are the meeting points of theology and dialogist as the confessors express themselves to God through dialogue. The dialogical spaces become sacred spaces because it is where dialogue partners encounter a common commitment to justice. Dialogues are not necessarily theological because non-Christian religions and natural sciences are encountered in and through dialogues. Intradisciplinary and/or interdisciplinary implications: This article acknowledges the realities of civil strife in the communities and that this strife creates walls between the people. A solution to this tension is that theology through dialogue should engage all sciences, natural or social, for harmonious co-existence within humanity.